Aging in America - H.W. Wilson Company (Ipswich, Massachusetts : H. W. Wilson, a division of EBSCO Information Services ; Amenia, NY : Grey House Publishing, 2014)
This volume examines the great challenges America will face in caring for aging baby boomers. The collection begins with statistical data on the major health issues for boomers, the demographics of the population, and the availability of health care in the future. How to negotiate rising medical costs and a growing population of seniors is one of the greatest challenges, the topic of the following chapter. The challenges and opportunities for families who care for aging parents is certain to be a developing issue in the future. The two following chapters examine progressive opportunities presented by an aging population. First, in the way perspectives on the senior years have evolved in the recent decade; second, on innovations in medicine that must respond to health care in the future. The final chapter compares America's response to an aging population with that of other counties in the world.
[4.] Redefining the senior years the changing perception of age. Boom : a generation explodes assumptions about aging / Maureen Hannan, Parks and Recreation, May 12, 2013 -- Newer tech on the rise with seniors / Laurenne Ramsdell, Foster's Daily Democrat, October 27, 2013 -- Careers : time for an encore for baby boomers / Dave Carpenter, Associated Press, September 9, 2012 -- Why are baby boomers leading the entrepreneurial movement? / Hanah Cho, Dallas Morning News, May 20, 2013 -- Living to 120 and beyond : Americans' views on aging, medical advances, and radical life extension / Pew Research, August 6, 2013 -- Why do grandmothers exist? solving an evolutionary mystery / Judith Schulevitz, The New Republic, February 11, 2013 -- Something more to say. . . / Catherine Jackson, Therapy Today, June 13, 2013 -- Death dinners at baby boomers' tables take on dying taboo / Shannon Pettypiece, Bloomberg, September 23, 2013 -- [5.] How living longer is advancing medicine and health care how science is extending life. We're living longer-and healthier / Alexandra Sifferlin, Time, July 29, 2013 -- Aging baby boomers want to live active lives, require innovations in medical treatment / Wendy Leonard, Deseret News, April 14, 2013 -- Innovation in senior care : "telegivers" help more seniors age at home / Husna Haq, Christian Science Monitor, April 13, 2011 -- How health tech can support the aging baby boomer population / Alicia Torres, Venturebeat.com, April 9, 2013 -- On beyond 100 / Stephen S. Hall, National Geographic, May 1, 2013 -- We're living longer / Larry Kusch, Winnipeg Free Press, October 26, 2013 -- [6.] An aging world population. The challenges and demands of an aging population -- An aging population may be what the world needs / Charles Kinney, Business Week, February 7, 2013 -- Global study : world not ready for aging population / Kristin Gelineau, Associated Press, September 30, 2013 -- Aging population more at risk from environmental threats / Gary Haq, The Conversation, October 28, 2013 -- Women living longer worldwide / Alexandra Sifferlin, Time, September 13, 2013 -- Major study finds that overall population health in U.S. has improved, but has not kept pace with other wealthy nations / Journal of the American Medical Association, September 10, 2013 -- How growth of elderly population in U.S. compares with other countries / Francesca Colombo, PBS.org, May 24, 2013 -- Do other countries take better care of the elderly? / Miriam Goodman, Examiner, November 9, 2011 -- Bank on it : is this volunteer program the solution to China's elder-care crisis? / Benjamin Shobert, Slate, November 5, 2013 -- Asia's new aging rich break family lies for gilded retirement / Rina Chandran, Bloomberg.com, November 20, 2013 -- Aging in Ghana : is it indeed a blessing or what? / Alhaji Alhasan Abdulai, GhanaWeb, November 18, 2013.
Includes bibliographical references and index.
Keywords: Older people -- United States; Older people -- Care -- United States; Older people -- Care -- Economic aspects -- United States; Aging -- Social aspects -- United States; Aging -- Economic aspects -- United States; Baby boom generation -- United States